(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Selective receivers improve solar-to-thermal conversion because they absorb short wave solar radiation efficiently while releasing very little long-wave thermal energy. This allows the receiver to hold more heat and deliver higher useful output. Research shows the same pattern across different solar thermal technologies, including flat-plate collectors, evacuated-tube collectors, parabolic trough systems, and dish or cavity receivers. Experimental studies highlight that selective coatings and well-designed receiver surfaces raise efficiency, strengthen high-temperature performance, and widen the operating range of each device. These improvements become more noticeable as the working temperature increases, making selective receivers important for both household systems and high-temperature concentrating applications.